Enhanced hydrolysis of excessive activated sludge by microwave - Chee, Kian Hao. (2009)
Sludge production has been steadily increased over the years. In U.S. alone, approximately 6.3 million metric tons of municipal wastewater sludge was produced in 1998. This is projected to increase to 6.9 million and 7.4 million metric dry tons in the years 2005 and 2010 respectively. Anaerobic digestion is responsible for sludge stabilization as well as the production of biogas in the form of methane. However, hydrolysis of waste activated sludge (WAS) is seen as the rate limiting step during sludge digestion. In this study, microwave treatment will be investigated as a possible technique for sludge disintegration. Microwave has the ability to excite dipolar molecules. Water, which is a dipolar molecule, is the main component of sludge. Theory wise the water molecules in the sludge should be readily excited when exposed to microwave. This should cause cellular disruption and speed up the hydrolytic process.